Gender Wise Distribution Of Body Composition, Blood Pressure And Haemoglobin Among Students Of Hotel Management Institute In India: A Pilot Study ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2017)
Background: Change in dietary pattern and a better economic situation in India has resulted in  non communicable diseases like heart ailments, diabetes, obesity etc. Irrespective of any age group,  children, adults, elderly population are at the risk of these health problems in India. Objective: To study the gender wise comparison of the health problems among Hotel Management students  in India. Methodology: Subjects (n=94) were selected through random sampling comprising of  both male and female in age group 18 to 25 years. A questionnaire was used to collect the data  regarding personal history and habits. Blood Pressure was monitored using sphygmomanometer.  Hemoglobin was measured using automated Heamoglobinometer. BMI (kg/m2) and Body Fat (BF%)  was measured using a commercially available digital weight scale incorporating a bioelectric  impedance analyzer (HBF-352, Omron Health care Co., Kyoto, Japan) based on bioelectric  impedance analysis. All statistical calculations were done using STATA IC 13 software. Results: Body Fat% was higher among females than males. Among both male and female students, dietary  habits were mostly non-vegetarian. Male students with non vegetarian dietary habits (88.7%)  were significantly higher than females (p
Keywords: Obesity; Hypertension; Gender Wise; BMI; Body Composition; Hotel Management